Pemberdayaan Perempuan Melalui Kelompok Wanita Tani di Kecamatan Sukoharjo: Empowering Women Through Women Farmers' Groups in Sukoharjo District - Defi Agustin Setya Luthfitah; Nurhadi Nurhadi; Bagas Narendra Parahita (Jurnal Sosiologi Agama Indonesia (JSAI), 2023)
This study aims to illustrate the empowerment of household women through Women Farmers Groups (Kelompok Wanita Tani, KWT) in Sukoharjo District, particularly in Kampung Ngromo. Employing qualitative methods, the study seeks to understand how KWT acts as an instrument for enhancing women's welfare and social roles. Through observation, interviews, and thematic data analysis, this study found that KWT contributes not only to the economic sector through agricultural activities and product processing but also strengthens its members' social networks and self-confidence. KWT Hesti Makarti and Kumalasari in Sukoharjo District, emerging from community initiatives, focus on improving family economics and environmental sustainability. Their involvement in various trainings and local competitions demonstrates increased competence and environmental awareness. However, the study also finds that while KWT aids in social and economic aspects, there are limitations in fully implementing the concept of women's empowerment. Abstrak Kajian ini bertujuan untuk menggambarkan tentang pemberdayaan perempuan Ibu Rumah Tangga (IRT) melalui Kelompok Wanita Tani (KWT) di Kecamatan Sukoharjo, khususnya Kampung Ngromo. Kajian ini menggunakan metode kualitatif untuk memahami bagaimana KWT menjadi instrumen untuk peningkatan kesejahteraan dan peran sosial perempuan. Melalui observasi, wawancara, dan analisis data tematik, hasil penelitian mengungkap bahwa KWT tidak hanya menghasilkan kontribusi ekonomi melalui kegiatan pertanian dan pengolahan produk, tetapi juga memperkuat jaringan sosial dan kepercayaan diri para anggotanya. KWT Hesti Makarti dan Kumalasari di Kecamatan Sukoharjo muncul dari inisiatif komunal, berfokus pada peningkatan ekonomi keluarga dan kelestarian lingkungan. Keterlibatan mereka dalam berbagai pelatihan dan lomba tingkat daerah menunjukkan peningkatan kompetensi dan kesadaran lingkungan. Namun, studi ini juga menemukan bahwa meskipun KWT berkontribusi dalam aspek sosial dan ekonomi, masih terdapat keterbatasan dalam menerapkan konsep pemberdayaan perempuan secara menyeluruh.